PERSEPSI PESERTA DIDIK TERHADAP PEMBELAJARAN SENI BUDAYA (TEATER) DI MAN 2 TANAH DATAR - Fachry Setia Nofanto; Titiek Fujita Yusandra (Universitas Negeri Padang, 2026)
This study aims to identify and describe students' perceptions of cultural arts (theatre) learning at MAN 2 Tanah Datar. This type of research is quantitative descriptive research. The instruments used in this study were questionnaires containing several statements, along with interviews and documentation. The stages of data analysis include data collection, data reduction, data presentation, and drawing conclusions. The results of this study proved that students have a very positive perception of cultural arts (theatre) learning at MAN 2 Tanah Datar. If the learning process is carried out and delivered well by the teacher and can be understood and accepted well by the students, it will also generate a good perception.